(3JNQjL JbQjH GdCSGfjOs - (3hdi GdOjf GdYQGbi CHi RQYI CMeO Hf YHO GdQMje Hf GdMSjf GdcQOi GdQGRjGfi Ke GdeUQjs; (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef GdYQGbj, Rjf GdOjf,J (B806 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH WhGa GdMGFV s
(3BNQgG (B:s
(3hjfJgi HBNQ GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B67 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B464s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs